Răspuns :
[tex]\sin \left(10^{\circ \:}\right)\cos \left(20^{\circ \:}\right)+\sin \left(20^{\circ \:}\right)\cos \left(10^{\circ \:}\right) \\ \\
Formula \cos \left(s\right)\sin \left(t\right)+\cos \left(t\right)\sin \left(s\right)=\sin \left(s+t\right) \\ \\
\sin \left(10^{\circ \:}\right)\cos \left(20^{\circ \:}\right)+\sin \left(20^{\circ \:}\right)\cos \left(10^{\circ \:}\right)=\sin \left(10^{\circ \:}+20^{\circ \:}\right) \\ \\
=\sin \left(30^{\circ \:}\right) \\ \\
=\frac{1}{2} \\ \\ \\
[/tex][tex]B) \cos \left(19^{\circ \:}\right)\cos \left(11^{\circ \:}\right)-\sin \left(19^{\circ \:}\right)\sin \left(11^{\circ \:}\right) \\ \\
Formula :: \cos \left(s\right)\cos \left(t\right)-\sin \left(s\right)\sin \left(t\right)=\cos \left(s+t\right) \\ \\
Deci \cos \left(19^{\circ \:}\right)\cos \left(11^{\circ \:}\right)-\sin \left(19^{\circ \:}\right)\sin \left(11^{\circ \:}\right)=\cos \left(19^{\circ \:}+11^{\circ \:}\right) \\ \\ \\
=\cos \left(30^{\circ \:}\right) \\ \\
=\frac{\sqrt{3}}[/tex]